Pengaruh Masa Pembungaan Pohon Sengon(Paraserianthes falcataria)Terhadap kandungan Pati di dalam Kayu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT The objective of this research is to observe the effect of flowering period and verti-- cally wood-trunk position to the starch content of Paraserianthes falcataria (sengon) trees. Research was conducted on '3 stems of P. faleataria tree, which consisted of one stem flowering period, one stem pre-flowering period and one stem post-flowering period. Each stem was cut into 3 parts, butt, middle and upper. The starch content of the wood was determined with Humphrey and Kelly method. Results show that vertically wood-trunk position influences the starch content. The higher position of the trunk produces lower starch content. Starch content of butt, middle and upper are 3.81%, 3.43% and 3.21% respectively. Starch content also varies according to flowering period. The highest starch content was found in pre-flowering period, the moderate in flowering period and the lowest in post-flowering period. Starch content of preflowering period, flowering period and post-flowering period are 3.88%, 3,57% and 3.00% respectively